EXPLORING PERFORMANCE MEASUREMENT SYSTEM FOR LECTURER (PMSL): COMPARISON AMONG THREE MODELS IN INDONESIA, SINGAPORE AND TURKEY - Hafiez Sofyani; Ietje Nazaruddin; Caesar Marga Putri; Erni Suryandari Fathmaningrum (Jurnal Reviu Akuntansi dan Keuangan, 2019)
This study aims at exploring the Performance Measurement System for Lecturer (PMSL) through a comparison study in three countries, namely Indonesia (MY), Singapore (IT), and Turkey (IMU). We uses multiple case study approach by conducting a comparative study. The data are obtained mainly using interview. Those lecturers assuming some offices and play some roles in formulating the lecturer performance policy are chosen to be this study’s informants, they are: Management and Organization Chair, Chairman of the university senate, Vice Rector for Academic Affair, and Member of Information Systems Audit Control. The results reveal that there are different PMSL patterns from the three research objects, i.e. MY (Indonesia), IT (Singapore) and IMU (Turkey). MY have fairly aggressive PMSL policy as compared to the other two campuses since they have to work harder to improve the performance of their lecturers who in this case have relatively lesser academic experiences at international level. MY reward special incentives for certain performance target and hold a science camp mentoring to improve their lecturers’ capabilities. Meanwhile, IT perform PMSL by classifying lecturer’s performance measurement into two tracks, namely teaching and research tracks. This makes lecturers more focused on and satisfied with their job, and eventually leads to an optimal performance level. Additionally, at IMU Turkey, to achieve lecturer optimal performance, the university prepares a policy related to three aspects: pedagogic (mentoring), knowledge management, and administration easiness. This research result is expected to give real contribution to the refinement of PMSL policy model at universities in Indonesia to allow it to trigger globally-competitive lecturer performance improvement (Global Achievement). This study explains how PMSL as a derivative of goal setting theory is effectively successfully implemented at a University in three different countries which in this case have different organizational cultures.